Determinants of Islamic Financial Planning for Young Couples’ Families in West Java - Az-Zahra, Nabilla; Fitri, Resfa; Alim, Ahmad Syahirul (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
West Java Province ranks highest in divorce rates in Indonesia, with economic factors being one of the main causes. This study is significant as research on Islamic financial planning among young couples remains limited, despite its potential to enhance household resilience. The objectives of this study are: (1) to analyze the characteristics of young couples in West Java in implementing Islamic financial planning for their families; and (2) to examine the influence of Islamic financial literacy, religiosity, and income perception on the intention and implementation of Islamic financial planning. The research employs a quantitative approach using descriptive analysis and Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that the majority of respondents demonstrate good financial awareness, as indicated by their possession of emergency savings. The respondents’ financial management priorities, based on the Charity, Investment, Debt, and Consumption (CIDC) framework, place charity as the highest priority, followed by investment, debt repayment, and consumption as the last priority. Income perception exerts a stronger influence on Islamic financial planning through the mediation of intention than through its direct effect. These findings recommend strengthening Islamic financial literacy through community-based educational programs, integrating related materials into pre-marital counseling, and leveraging digital media to enhance family economic stability and reduce divorce rates caused by economic issues.